RELEVANSI TEORI KOMUNIKASI HABERMAS DALAM PENDIDIKAN - PURWASTUTI, LUSILA ANDRIANI (Universitas Negeri Yogyakarta, 2005)
Habermas's view of communication theorv can he an alternative solution to the current critical situation particularly in Indonesia, which is facing conflicts in a variety of dimensions. Hahermas's wise view that can be referred to is that there is no absolute truth. There is no single absolute way to solve a variety of crises resulting from conflicts. To create a more humane world, the suggested way is communication, a dialectical positive model. We should make an attempt together to create a liberating path on the basis of the high humanistic values that we search together. Education is also a communication process Therejore, essentially, the communication conditions should he applied in the field qj education. This is expected to create a liberating path to empower adult learners.